Video explainer, e-module, or both: which is better to improve statistics performance of graduate students? - Roberto G. Sagge Jr.; Salvador P. Bacio Jr. (International Journal of Evaluation and Research in Education (IJERE), 2024)
Technology is an essential component of modern education, and teachers use various types of technology to improve classroom performance. Meanwhile, statistics is one of the seemingly difficult courses according to students across levels. This study experimental aimed to determine if video explainer and e-module improve students’ performance in statistics. There were 78 graduate school students participated and used video explainer, e-module, or both as an intervention. A 100-item performance test in statistics was used. The statistical techniques employed were mean, standard deviation and analysis of covariance (ANCOVA). Results revealed that students’ pre-test performance was “average”. Additionally, their posttest performance was “high”, regardless of the intervention utilized. Significant differences emerged between groups who utilized both video explainer and e-module and those who used simply video explainer or e-module. Video explainer and e-modules should be integrated carefully into the instruction, helping graduate students develop a solid understanding of statistics. The results of the study suggest that studying statistics is more successful when one uses these interventions because it integrates visuals, audio, real-world applications, accessibility and flexibility towards various learning styles. Learning stakeholders should cooperate to ensure seamless integration of these materials into the curriculum and provide ample support to educators in generating and managing content.Technology is an essential component of modern education, and teachers use various types of technology to improve classroom performance. Meanwhile, statistics is one of the seemingly difficult courses according to students across levels. This study experimental aimed to determine if video explainer and e-module improve students’ performance in statistics. There were 78 graduate school students participated and used video explainer, e-module, or both as an intervention. A 100-item performance test in statistics was used. The statistical techniques employed were mean, standard deviation and analysis of covariance (ANCOVA). Results revealed that students’ pre-test performance was “average”. Additionally, their posttest performance was “high”, regardless of the intervention utilized. Significant differences emerged between groups who utilized both video explainer and e-module and those who used simply video explainer or e-module. Video explainer and e-modules should be integrated carefully into the instruction, helping graduate students develop a solid understanding of statistics. The results of the study suggest that studying statistics is more successful when one uses these interventions because it integrates visuals, audio, real-world applications, accessibility and flexibility towards various learning styles. Learning stakeholders should cooperate to ensure seamless integration of these materials into the curriculum and provide ample support to educators in generating and managing content.